Relationship of gynaecologic cancer stage and poverty - Gutiérrez, César (2008)
Objective: To determine the relationship between poverty and stage at diagnosis of gynaecologic cancer. Design: Multiple groups ecologic study. Setting: Instituto Nacional de Enfermedades Neoplasicas (INEN – National Institute of Cancer). Participants: Women with both cervical and breast cancer. Methods: From 2000-2004 INEN statistics registry we determined the proportion of patients from Lima and Callao who sought care for both cervical and breast cancer advanced stages (III and IV). We registered the patients’ district of origin poverty level by using the 2006 Foncodes poverty map, ranking the districts of Lima and Callao in deciles according to the deprivation index. The Spearman correlation coefficient was calculated to establish the proportion of patients with advanced stage of a gynaecologic cancer and the level of poverty. Main outcome measures: New cases of both breast and cervical cancer and poverty. Results: During the period studied there were 2 956 new cases of breast cancer and 2 547 new cases of cervical cancer; 50,7% of breast cancer and 44,1% of cervical cancer cases sought care with an advanced stage of the disease. A statistically significant direct correlation was found between poverty level and advanced cases of breast cancer (rho = 0,81, p<0,001) and between poverty and advanced cases of cervical cancer (rho=0,92, p<0,001). Conclusions: We found a strong correlation between poverty level and advanced cases of gynaecologic cancer in patients attended at INEN in the period 2000-2004. This could be an indicator of access inequality to health services in the population of Lima and Callao.